Retailer Competition - Oggioni, Giorgia; Schwartz, Alexandra; Zöttl, Gregor; Wiertz, Ann-Kathrin (2021)
We consider strategic retail pricing in markets where retailers buy commodities at fluctuating wholesale prices and resell them by applying dynamic retail tariff, such as real–time pricing, to final consumers. These tariffs are defined in such a way that they can reflect, to some extent, the wholesale price fluctuations and might increase market efficiency and retailers'profits. This paper provides important modelling approaches and insights regarding dynamic retail tariffs. This is of especially large relevance in the light of current efforts to implement dynamic retail pricing schemes in liberalized energy markets worldwide. From a modelling point of view, we propose a multi-leader-follower problem to investigate the implications of strategic retail pricing and we compare the impacts of the implementation of both fixed price tariffs and dynamic tariffs on final consumers. Moreover, we develop algorithms which solve the multi- leader-follower problems for general setups and allow us to characterize the resulting market equilibria. In addition, for specific symmetric setups we are able to provide explicit analytical solutions. The analytical and numerical results obtained for our framework show that, in those cases where strategic competition among retailers plays little role, dynamic real-time pricing increases market efficiency and retailer profits as compared to fixed-tariff pricing. This confirms the existing results which do not explicitly model strategic retail competition. However, if strategic competition among retailers plays an important role, the application of real-time pricing can reduce market efficiency and retailer profits with respect to fixed-tariff pricing, as our detailed strategic analysis highlight